Drug-induced mast cell eradication: a novel approach to treat mast cell activation disorders? - Valent, Peter; Akin, Cem; Hartmann, Karin; Reiter, Andreas; Gotlib, Jason; Sotlar, Karl; Sperr, Wolfgang R.; Degenfeld-Schonburg, Lina; Smiljkovic, Dubravka; Triggiani, Massimo; Horny, Hans-Peter; Arock, Michel; et al. (The journal of allergy and clinical immunology, 2022)
Mast cell (MC) activation is a key event in allergic reactions, other inflammatory states, and MC activation syndromes. MC-stabilizing agents, mediator-targeting drugs, and drugs interfering with mediator effects are often prescribed for these patients. However, the clinical efficacy of these drugs varies depending on the numbers of involved MCs and the underlying pathology. One straightforward approach would be to eradicate the primary target cell. To date however, no MC-eradicating treatment approach has been developed for patients with MC activation disorders. Nevertheless, recent data suggest that long-term treatment with agents effectively inhibiting KIT function results in the virtual eradication of tissue MCs and a sustained decrease in serum tryptase levels. In many of these patients, MC depletion is associated with a substantial improvement in mediator-induced symptoms. In patients with an underlying KIT D816V-positive mastocytosis, such MC eradication requires an effective inhibitor of KIT D816V, such as avapritinib. However, the use of KIT inhibitors must be balanced against their potential side effects. Here we discuss MC-eradicating strategies in various disease models, the feasibility of this approach, available clinical data, and future prospects for the use of KIT-targeting drugs in MC activation disorders.